HEART FUNCTIONAL INDICATORS IN HAND WORKERS - Medvedev, I.N.; Mikhailova, I.V.; Mikhailov, A.A.; Rysakova, O.G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to find out the features of the function of the left ventricle of the heart in systematically trained hand-to-hand fighters. Methods and structure of the study. The observation was made on 23 well-trained hand-to-hand young men with at least four years of uninterrupted sports experience. The control group included 27 healthy male volunteers who had never been involved in physical culture and sports. The examination included an ultrasound assessment of the heart using an SSD-80 Aloka echocardiograph (manufactured in Japan) with the registration of a number of heart parameters. Mathematical processing of the results was performed by Student's t-test by computer data processing. Results and conclusions. The examined hand-to-hand fighters showed signs of hypertrophy of the left ventricular myocardium, manifested by an increase in its mass and an increase in the thickness of its posterior wall. However, its overall size and cavity volume remained normal. Hand-to-hand fighters were characterized by a high rate of myocardial relaxation, exceeding this indicator in untrained young men. The results obtained allow us to consider that hand-to-hand combat exercises strongly stimulate the entire body. This ensures the development of a physiologically very beneficial increase in the mass of the left ventricular myocardium while maintaining the optimum of its functional characteristics and the normal volume of its cavity.